2023
DOI: 10.3390/ijerph20042782
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emotional Regulation, Resilience, and Distress Disclosure on Post-Traumatic Growth in Nursing Students

Abstract: Nursing students, who need to reflect on self, secure their identity, and be prepared as would-be nurses, can make a good use of post-traumatic growth (PTG) that can function as a catalyst for positive change even amidst this COVID-19 crisis. Emotional regulation strategies in traumatic events are key factors for successful growth, resilience is positively associated with PTG, and distress disclosure is an important factor for stress reduction. In this context, this study is a descriptive research study to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…91 Resilience positively influences communication skills, previous studies show that this ability is the most effective way to cope in the face of an external threat. 49,92,93 Therefore, it is necessary for organizations to adopt strategies to increase the capacity to develop resilience in staff to cultivate communication skills. 49 Given that, resilience acts as a buffer against job stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…91 Resilience positively influences communication skills, previous studies show that this ability is the most effective way to cope in the face of an external threat. 49,92,93 Therefore, it is necessary for organizations to adopt strategies to increase the capacity to develop resilience in staff to cultivate communication skills. 49 Given that, resilience acts as a buffer against job stress.…”
Section: Discussionmentioning
confidence: 99%
“…49,92,93 Therefore, it is necessary for organizations to adopt strategies to increase the capacity to develop resilience in staff to cultivate communication skills. 49 Given that, resilience acts as a buffer against job stress. 94 Nurses with greater resilience have strong communication skills, as they are able to express themselves in the face of various stressful events and seek support from colleagues, friends, or family members, helping to maintain greater mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, studies of adolescent DD have yielded mixed results. Some suggest that disclosing trauma can span the spectrum of traumatic symptoms and lead to benefits such as emotional relief, social support, improved coping strategies, and increased resilience (Keum et al, 2023;Kim et al, 2023). However, others highlight that some adolescents regret disclosing abuse, sometimes facing negative repercussions (Jacques-Tiura et al, 2010;Sousa et al, 2023).…”
Section: Dd and Trauma Symptommentioning
confidence: 99%
“…Resilience is a psychological resource that refers to positive adaptation and functioning in the face of a crisis [15,16]. Studies conducted during the COVID-19 pandemic found that teachers' resilience was positively related to their emotional state and functioning [11,17], and that resilience is a significant positive predictor of teacher well-being [18].…”
Section: Introductionmentioning
confidence: 99%